A tutela jurídica do equilíbrio ambiental em face do pacto federativo - Santos, Luzia do Socorro Silva dos (2008)
In this thesis we investigated the legal protection of the environment under the Brazilian federative agreement, as we analyzed the constitutional and infraconstitutional rules that are related to these two phenomena in order to check the necessity of attributing an interpretation of the constitutional precepts which promote the political centralization or decentralization, according to the current society requirements which are characterized by dangers and risks. The main theoretical points were presented as follows: a) that the legal protected asset is the human and ecologically balanced environment, whose property is diffuse; b) that the constitutional system of sharing and competencies obligate all federate beings to act simultaneously in order to promote the protection of the environment, according to the administrative and legislative power conferred by the current federal Constitution; c) that the protected environmental asset contributes to promoting sustainable human development aprioristically related to the main objectives of the Federative Republic of Brazil, that are predicated in the third article of the constitutional text, which refers to the main goal of the Brazilian government. The results showed that environment degradation is also found in the social and regional inequalities that exist in the country. The regeneration demands coordinated actions, which shout also be cooperative and jointly supportive amongst the federate beings, according to the democratic principle. Therefore, the affirmation of the state action as the leading manager of the environmental risks currently demands the development of legal institutes which promote the decentralization of the political power on behalf of the autonomy of the partial wills in view of the exclusive control practised by the central will on environmental relevant resources. We proposed, amongst other suggestions, that the regional and local environment would serve as an interpretative vector for the determination of the state and municipal competences and that the law of directives on the planning of the national development would guarantee the binding participation of the federate beings, as well as the political responsibilities to be applied as an instrument for the collective environmental protection